2021
DOI: 10.1007/s11606-021-06973-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Discussing Life Expectancy: a Systematic Review

Abstract: BACKGROUND: Discussing life expectancy helps inform decisions related to preventive medication, screening, and personal care planning. Our aim was to systematically review the literature on patient preferences for discussing life expectancy and to identify predictors for these preferences. METHODS: We searched PubMed, Cochrane Library, Embase, MEDLINE, PsycInfo, and gray literature from inception until 17 February 2021. Two authors screened titles/abstracts and full texts, and extracted data and one author ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 64 publications
(291 reference statements)
0
21
0
Order By: Relevance
“…Bjork et al’ s review on a total of 41 studies consisted of 23 quantitative survey and 14 qualitative interview studies 1. ‘Willingness to discuss life expectancy ranged from 19% to 100% (median 61%, IQR 50–73) across studies with the majority (77%) reporting more than half of subjects willing to discuss.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bjork et al’ s review on a total of 41 studies consisted of 23 quantitative survey and 14 qualitative interview studies 1. ‘Willingness to discuss life expectancy ranged from 19% to 100% (median 61%, IQR 50–73) across studies with the majority (77%) reporting more than half of subjects willing to discuss.…”
Section: Resultsmentioning
confidence: 99%
“…Bjork et al 1 searched literature in PubMed, Cochrane Library, Embase, MEDLINE and PsycInfo for keywords pertaining to life expectancy, patient preferences and communication. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, authors included articles that reported on patient discussion of life expectancy issues across various patient groups 1. Meta-analysis was not performed 1…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations